Impossible ‘qui pro quo’: Fedor Dostoevsky and Zinaida Gippius (the short story “Ivan Ivanovich and the Devil”) - Iana Ia. Dzhamalova (Слово.ру: балтийский акцент, 2024)
This paper analyses the operation of the ‘qui pro quo’ principle in Zinaida Gippius's story “Ivan Ivanovich and the Devil.” Rooted in a comedic literary device based on misunderstanding and confusion, the ‘qui pro quo principle’ was identified by Rita Kleyman as a key element in the poetics of Fedor Dostoevsky's works, particularly in his novel “The Brothers Karamazov”. Scholars have frequently noted the connection between Gippius's story and Dostoevsky’s novel. However, the presence of another link — the ‘qui pro quo principle’ — has yet to be explored in Gippius's text. The analysis demonstrates that the principle manifests through the symbolic pairing of the main characters and is closely tied to the theme of temptation. The use of the ‘qui pro quo’ principle in the story results in an inverted portrayal of the motif of temptation. It is argued that one of the defining characteristics of Gippius's imagery — the contradictory nature of the protagonists — is shaped by this principle. The ‘qui pro quo’ is a constant feature of Dostoevsky's works and is reinterpreted by Gippius. The principle is an additional thread linking 19th-century Russian classical literature with Russian modernist literature.